Structural basis of metallo-β-lactamase, serine-β-lactamase and penicillin-binding protein inhibition by cyclic boronates - Jürgen Brem (Nature Portfolio, 2016)
Bacterial beta-lactamases are responsible for resistance to beta-lactams, the most important family of antibiotics. Here, the authors reveal cyclic boronate inhibitors that are active against both serine- and metallo-beta-lactamases and represent a promising strategy for combined antimicrobial treatments.